Essential Oil Plants Growing in the Surkhandarya Region - H.K.Dzhumayev; G.E. Umirzakova (Genius Journals, 2023)
The amount of essential oils collected from the surface, leaves and flowers of several types of essential oil plants growing in different phases in Surkhandarya region was determined. Compared to the amount of essential oils collected in the vegetative phase, it was found that the amount of essential oils is slightly more collected in the gross flowering phase
Keywords: Asteraceae; Lamiaceae; Apiaceae; flora